DIAGNOSIS AND TREATMENT: WILSON’S DISEASE - Trufanov, Ye.O. (World of Medicine and Biology, 2018)
Wilson’s Disease is a chronic hereditary, autosomal-recessive disorder associated with excessive deposition of copper in the liver, brain, and other tissues. Despite of a characteristic clinical picture, diagnostics of Wilson’s Disease is complicated. Diagnosis delay and untimely initiation of treatment lead to a rapid progression of neurological symptoms, pathological changes in the liver and patient’s death for several years. Adequate, continuous treatment (diet, penicillamine) initiated in the early stages of the disease greatly improves clinical symptoms and the prognosis of Wilson’s Disease.